Shaping Evidence-Based Hand Hygiene Policies for a Healthier Future: Assessing Community Awareness in Ras Al Khaimah’s Educational Institutions and Public Spaces - Patrick Saliba (Al Qasimi Foundation, 2026)
Hand hygiene is widely recognized as one of the most effective and cost-efficient public health measures for preventing the transmission of infectious diseases. This policy paper provides one of the first comprehensive assessments of community hand hygiene awareness in Ras Al Khaimah. Findings reveal a strong foundation of community awareness regarding the importance of hand hygiene and demonstrate that the Emirate is well positioned to build upon existing public awareness through targeted, evidence-informed public health policies. By establishing a baseline assessment of community awareness, knowledge, behaviors, environmental influences, and perceived barriers, the paper offers a practical framework for prioritizing future interventions and evaluating their impact over time.